1992
DOI: 10.1007/bf02893012
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential areas for the occurrence of strong earthquakes in Himalayan arc region

Abstract: Morphostructural zoning (MSZ) scheme of the Himalayan arc region as obtained from a joint study of topographic, geological and tectonic maps as well as satellite imagery is analysed. Three types of morphostructures have been determined: territorial units (blocks of different ranks), linear zones limiting these blocks (lineaments) and intersections of the lineaments (knots). Comparison of MSZ scheme with the known seismicity indicates epicenters of strong earthquakes (M/> 6.5) clustered around some of these kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 6 publications
1
25
0
1
Order By: Relevance
“…Other knots also partially overlap some parts of Area A. Dangerous knots of Bhatia et al (1992) are either within area A or are at boundary of A, which implies a similarity in identification of almost same areas by different methods. In addition, Area A is much larger than the area encompassed by knots.…”
Section: Results and Interpretationmentioning
confidence: 94%
See 3 more Smart Citations
“…Other knots also partially overlap some parts of Area A. Dangerous knots of Bhatia et al (1992) are either within area A or are at boundary of A, which implies a similarity in identification of almost same areas by different methods. In addition, Area A is much larger than the area encompassed by knots.…”
Section: Results and Interpretationmentioning
confidence: 94%
“…These are located in Doda district of J&K and Chamba district of HP. Bhatia et al's (1992) qualitative study for the occurrence of strong earthquakes identifies potential areas as dangerous knots in the Himalayan arc. The quantitative approach of the present study has identified three kinds of seismically susceptible areas in western Himalayas where Area A is the most susceptible.…”
Section: Results and Interpretationmentioning
confidence: 99%
See 2 more Smart Citations
“…For this purpose, the methodology developed by IIEPT&MG that has been applied to many seismic regions of the world for the identification of seismogenic nodes has been employed (Bhatia et al 1992;Gelfand et al 1972Gelfand et al , 1976Gorshkov et al 1991Gorshkov et al , 2000Gorshkov et al , 2002Gorshkov et al , 2003Gorshkov et al , 2004Gvishiani et al 1986Gvishiani et al , 1987Gvishiani et al , 1988. Recent earthquakes in each of the regions studied have proven the reliability of the results obtained.…”
Section: Morphostructural Zoning (Mz) Methodsmentioning
confidence: 99%